2007
DOI: 10.1111/j.1530-0277.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymocytes, Pre‐B Cells, and Organ Changes in a Mouse Model of Chronic Ethanol Ingestion—Absence of Subset‐Specific Glucocorticoid‐Induced Immune Cell Loss

Abstract: This model of ethanol administration is convenient, sustainable for up to 1 year, demonstrably feasible in several mouse strains, permits good weight gains in most strains, and results in significant changes in a number of organs. The administration method also will permit modeling of long-term steady abuse punctuated by major binges, and is suitable for supplementation studies using water soluble additives. Overall, the method is useful for a wide range of studies requiring a chronic low-stress method of etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 70 publications
6
82
0
1
Order By: Relevance
“…Overall, chronic ethanol selfadministration did not modulate the frequency or subset distribution of circulating lymphocytes. This observation is consistent with some reports of chronic ethanol exposure in rodents, NHPs and humans [8,34,35]. Nonetheless, other studies have reported significant perturbations of both the number and frequency of peripheral T and B cells with either acute or chronic alcohol exposure (reviewed by [34,36]).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, chronic ethanol selfadministration did not modulate the frequency or subset distribution of circulating lymphocytes. This observation is consistent with some reports of chronic ethanol exposure in rodents, NHPs and humans [8,34,35]. Nonetheless, other studies have reported significant perturbations of both the number and frequency of peripheral T and B cells with either acute or chronic alcohol exposure (reviewed by [34,36]).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with some reports of chronic ethanol exposure in rodents, NHPs and humans [8,34,35]. Nonetheless, other studies have reported significant perturbations of both the number and frequency of peripheral T and B cells with either acute or chronic alcohol exposure (reviewed by [34,36]). It has been suggested that ethanolinduced lymphocyte depletion is mediated by the action of stress-induced glucocorticoids, particularly corticosterone in rodents, on developing lymphocytes (reviewed by [34]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…33 We have not address this in detail but in the study by Cook et al 34 , using a similar regimen of alcohol exposure (ad libitum access in the drinking water) but for a much longer period and with a 2-fold higher dose than ours, it was found that mice had reduced heart weight, mild steatosis, altered gut flora, increased serum levels of peptidoglycan, whereas many other parameters/ organs like alanine aminotransferase activity, pancreas, corticosterone or peripheral blood parameters were not altered.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were administered EtOH using the Meadows-Cook model of administration (Cook et al, 2007, Cook et al, 2004, Gurung et al, 2009, Meyerholz et al, 2008, Song et al, 2002, Parlet and Schlueter, 2013. After 1 week of acclimation, mice were separated into two groups of equal size.…”
Section: Etoh Administrationmentioning
confidence: 99%